Collaborative Planning, Forecasting, and Replenishment (CPFR) to Reduce Bullwhip Effect: Case Study - Tarigan, Indah Rizkya; Tambunan, Mangara Mangapul; Rimbawan, Ericko Wasita (Jurnal Sistem Teknik Industri, 2023)
Supply chain is basically an integrated system in the process of preparing and delivering products to consumers. This chain is also a network of numerous businesses that are interrelated and have a common objective. This company, which is engaged in the processing of soy sauce using soybeans as its raw material, produces sweet soy sauce and salty soy sauce. Production policy used in this industry was based on the number of requests at the store's sales area and the demand to anticipate fluctuating demand were added 10%. Inaccuracies in the number of requests result in a varied difference between the number of requests and the number of sales, causing overstocking when demand decreases or stockouts when supplies cannot meet demand or commonly known as the bullwhip effect. Based on these problems, this study aims to obtain the right production policy to minimize the bullwhip effect using the CPFR framework. The results of this study show that the bullwhip effect values ​​for sweet and salty soy sauce are 0.812 and 0.814, respectively.